Pismanta geothermal play in the iglesia basin related to transverse fault systems in the andean orogen. (January 2023) - Clavel, Franco G.; Gonzalez, Marcelo; Gianni, Guido M.; Winocur, Diego; Christiansen, Rodolfo O.; Lince Klinger, Federico; Martinez, Myriam P.
Abstract: The intermontane Iglesia Basin constitutes the northern Uspallata-Calingasta-Iglesia tectonic depression that holds the Pismanta geothermal field, genetically connected with the basin evolution and structure. Understanding the local structure associated with this geothermal field and linking this system to the regional tectonics is essential to characterize thermal water rising in this area. To address this issue, we carried out a field-based structural analysis and an examination of sedimentary outcrops at the Pismanta area. Also, we linked surface structural data to the subsurface basin structure by means of a previously interpreted seismic reflection line. Our integrated analysis reveals that the Pismanta geothermal field is located in an area of favorable lithology at the intersection of WNW- and NNE-trending thrust faults. These jointly developed a permeability anomaly zone at the Pismanta locality that allows hot underground water rising from deep sedimentary sequences. This observation explains why the thermal springs are only locally concentrated in the study area; a key aspect that was not taken into account in previous models for the Pismanta geothermal field. These results and the overall basin tectonic evolution allowed us to define a new and more complex structural geothermal play model at the Pismanta field. Highlights: Iglesia basin is a tectonic depression that holds the Pismanta geothermal field. This system is genetically connected with the early basin evolution and structure. The presence of a favorable lithology at the intersection of WNW-, NNE-structures. The damaged zone developed a permeability anomaly area at the Pismanta locality. The tectonic evolution allowed us to define the Pismanta geothermal play.